PEMETAAN KANTOR PEMBIAYAAN BERBASIS WEBSITE PADA KANTOR PELAYANAN PERIJINAN TERPADU - F, Farid (Program Vokasi Universitas Negeri Gorontalo, 2025)
The objective of this research is to design and develop a Geographic Information System (GIS) to systematically visualize and map locations of financing offices in Gorontalo City, focusing on the Integrated Licensing Service Office (KPPT). The study addresses the lack of clear geographic information regarding financing office locations, which hinders access to financial services. A descriptive method was used, with a System Development Life Cycle (SDLC) review to define system requirements. The result is a web-based application that provides interactive access to financing office locations via a map. System testing using white-box and black-box methods confirmed that the system is free from logical errors and meets functional requirements. The findings indicate that GIS enhances information accessibility for the Gorontalo community regarding financing offices. The study highlights the benefits of Information system developments and suggests further enhancements using shortest path algorithms to improve location search efficiency.